2004
DOI: 10.1016/s1474-4422(04)00852-x
|View full text |Cite
|
Sign up to set email alerts
|

Brain function in coma, vegetative state, and related disorders

Abstract: We review the nosological criteria and functional neuroanatomical basis for brain death, coma, vegetative state, minimally conscious state and the locked-in state. Functional neuroimaging is providing new insights into cerebral activity in patients with severe brain damage. Measurements of cerebral metabolism and brain activations in response to sensory stimuli using positron emission tomography (PET), functional magnetic resonance imaging (fMRI) and electrophysiological methods have significant potential to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

36
562
1
46

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 885 publications
(667 citation statements)
references
References 98 publications
(69 reference statements)
36
562
1
46
Order By: Relevance
“…In the past 15 years, functional neuroimaging [e.g., positron emission tomography and functional MRI (fMRI)] and cognitive evoked potential studies have offered the possibility to measure directly and non-invasively severely brain damaged patients' brain activity at rest and during external activation (for review, see [58]). More recently, however, these techniques have been developed aiming to detect neural (motor-independent) command following.…”
Section: Para-clinical Neuroimaging Assessment Independent Of Motor Rmentioning
confidence: 99%
“…In the past 15 years, functional neuroimaging [e.g., positron emission tomography and functional MRI (fMRI)] and cognitive evoked potential studies have offered the possibility to measure directly and non-invasively severely brain damaged patients' brain activity at rest and during external activation (for review, see [58]). More recently, however, these techniques have been developed aiming to detect neural (motor-independent) command following.…”
Section: Para-clinical Neuroimaging Assessment Independent Of Motor Rmentioning
confidence: 99%
“…FDG-PET studies have demonstrated that when patients recover from coma to VS/UWS, they recover the wakefulness network (encompassing brainstem and basal forebrain) which explains the restoration of sustained spontaneous or stimulus-induced eye opening and of autonomic functions including spontaneous breathing [18]. However, recovery from VS/UWS does not coincide with near-normal metabolic activity in overall brain function.…”
Section: Tracking the Recovery Of Consciousness Networkmentioning
confidence: 99%
“…Posterior cingulate and adjacent precuneal cortices were reported to show most impaired metabolism in UWS/VS (Laureys et al, 1999) and seem to differentiate MCS from UWS/VS patients (Laureys et al, 2004). More recently, a study on patients in the chronic stage of traumatic diffuse brain injury confirmed this bilateral frontoparietal hypometabolism and showed that these regions were more dysfunctional in UWS/VS than MCS patients (Nakayama et al, 2006).…”
Section: Discussionmentioning
confidence: 93%